1987
DOI: 10.1172/jci112961
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rat skeletal muscle branched-chain alpha-keto acid dehydrogenase in vivo. Effects of dietary protein and meal consumption.

Abstract: The effects of dietary protein on the activity of skeletal muscle branched-chain a-keto acid dehydrogenase (BCKAD) were investigated. BCKAD is rate-limiting for branched-chain amino acid (BCAA) catabolism by muscle; its activity is modulated by phosphorylation-dephosphorylation. In rats fed an adequate protein (25% casein) diet, BCKAD was -2% active postabsorptively and increased to 10% or 16% active after a 25% or 50% protein meal, respectively. Prolonged feeding of a 50% protein diet increased postabsorptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In contrast, the SC of isoleucine and valine in pigs fed the 120 and 160% Leu:Lys ratios decreased to less than 50% of that in pigs fed the diet with the 88% ratio. These results are also consistent with previous reports (Edmonds and Baker, 1987;Wiltafsky et al, 2010), resulting from increased activity of the enzyme complex that catabolizes all 3 branched chain amino acids in pigs fed diets with excess Leu (Block et al, 1987;Wiltafsky et al, 2010). Furthermore, competitive inhibition for absorption among branched chain amino acids has been documented (Hagihira et al, 1961).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the SC of isoleucine and valine in pigs fed the 120 and 160% Leu:Lys ratios decreased to less than 50% of that in pigs fed the diet with the 88% ratio. These results are also consistent with previous reports (Edmonds and Baker, 1987;Wiltafsky et al, 2010), resulting from increased activity of the enzyme complex that catabolizes all 3 branched chain amino acids in pigs fed diets with excess Leu (Block et al, 1987;Wiltafsky et al, 2010). Furthermore, competitive inhibition for absorption among branched chain amino acids has been documented (Hagihira et al, 1961).…”
Section: Discussionsupporting
confidence: 93%
“…While control rats habitually consumed all their food in less than 23h and may have experienced a food-deprivation period on a daily basis, the rats fed the -Arg/+Ala diet, in contrast, always had food available. The rate-limiting enzyme for BCAA catabolism, branched-chain ketoacid dehydrogenase (BCKADH), has been shown to be more active in meal-fed rats than in rats allowed ad libitum consumption of diet (Block et al, 1987). Therefore, greater activity of BCKADH may have catabolized more BCAA in muscles of rats fed +Arg or -Arg/+Cit diet.…”
Section: Effects' Of Diet On Muscle Free Amino Acid Concentrationsmentioning
confidence: 99%
“…To determine the maximal activity of BCKA dehydrogenase, the enzyme was fully activated by incubating tissue homogenates with 5 mM Mg2e for 15 min at 37°C before measurement of activity. We and others (10,24,25) have previously shown that this method of activating the enzyme is effective.…”
Section: Methodsmentioning
confidence: 87%
“…Abbreviations used in this paper: BCAA, branched chain amino acids; BCKA, branched chain keto acids. protein content has a profound effect on BCAA catabolism (7)(8)(9)(10)(11). In contrast, the effect of dietary carbohydrate and fat on BCAA metabolism has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%